2015
DOI: 10.1186/s12885-015-1424-5
|View full text |Cite
|
Sign up to set email alerts
|

The Danish cancer pathway for patients with serious non-specific symptoms and signs of cancer–a cross-sectional study of patient characteristics and cancer probability

Abstract: BackgroundA Danish cancer pathway has been implemented for patients with serious non-specific symptoms and signs of cancer (NSSC-CPP). The initiative is one of several to improve the long diagnostic interval and the poor survival of Danish cancer patients. However, little is known about the patients investigated under this pathway. We aim to describe the characteristics of patients referred from general practice to the NSSC-CPP and to estimate the cancer probability and distribution in this population.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
180
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(194 citation statements)
references
References 34 publications
11
180
3
Order By: Relevance
“…Recent research has highlighted the range of biopsychosocial, contextual, and cultural influences on the ways in which people recognise, interpret, and act on symptoms. 21 The findings of this study add to this by suggesting that further influences, such as comorbidity, can complicate the diagnosis, as patients may not recognise symptoms as indicative of cancer and GPs may not act on them due to the known comorbidity. The authors also found that some patients experienced a 'gut feeling' that further influenced their diagnosis pathway.…”
Section: Comparison With Existing Literaturementioning
confidence: 57%
“…Recent research has highlighted the range of biopsychosocial, contextual, and cultural influences on the ways in which people recognise, interpret, and act on symptoms. 21 The findings of this study add to this by suggesting that further influences, such as comorbidity, can complicate the diagnosis, as patients may not recognise symptoms as indicative of cancer and GPs may not act on them due to the known comorbidity. The authors also found that some patients experienced a 'gut feeling' that further influenced their diagnosis pathway.…”
Section: Comparison With Existing Literaturementioning
confidence: 57%
“…Currently, 18 F-FDG PET/CT is not recommended as the primary method for investigation in this group of patients (24). However, because the estimated prevalence of cancer in patients referred to DOC is approximately 10-fold higher than in the abovementioned studies (9,10), the FP rate is expected to be substantially lower and 18 F-FDG PET/CT cannot be ruled out as the best firstline imaging modality in a high-cancer-prevalence population. Furthermore, the most common noncancer findings in this population of patients are rheumatoid or infectious diseases for which 18 F-FDG PET/CT has shown a better detection rate than routine CT (27).…”
mentioning
confidence: 99%
“…The referral was typically prompted by one or more of the following observations: increasing health service-seeking behavior; weight loss; tiredness; or a group of unspecific symptoms, which did not fit into any of the organ-specific established cancer investigation programs. A cancer prevalence of 16%-18% was found in patients investigated at DOC for NSSC in Denmark (9,10).…”
mentioning
confidence: 99%
“…A need for a process-oriented quality program like DQM remains, even though formally DQM has been abolished for Danish hospitals (the secondary health care sector). National political decisions result in new aims and goals, such as the Danish cancer pathway program (Ingeman et al, 2015). Initiated by parliament, it offers all patients a national standard program within guaranteed deadlines.…”
Section: Meeting Pointmentioning
confidence: 99%